Making Meaningful Connections and Relationships in Cataloguing Practices: The Decolonizing Description Project at University of Alberta Libraries - Laroque, Sheila (Evidence Based Library and Information Practice, 2018)
Overview This paper seeks to examine some of the history behind the work that led to the Decolonizing Description Working Group (DDWG) and the efforts that have come from the further Decolonizing Description Project at the University of Alberta Libraries (UAL). Within universities and a variety of memory institutions, there has been a shift since the Calls to Action of the Truth and Reconciliation Commission (TRC) report (2015). This paper seeks to give those who are interested in this type of work some insight into the processes that have been underway at the UAL, and into ways that this could be replicated within their own institutions.